2020
DOI: 10.3390/ijms21072483
|View full text |Cite
|
Sign up to set email alerts
|

Female AhR Knockout Mice Develop a Minor Renal Insufficiency in an Adenine-Diet Model of Chronic Kidney Disease

Abstract: Cardiovascular complications observed in chronic kidney disease (CKD) are associated with aryl hydrocarbon receptor (AhR) activation by tryptophan-derived uremic toxins—mainly indoxyl sulfate (IS). AhR is a ligand-activated transcription factor originally characterized as a receptor of xenobiotics involved in detoxification. The aim of this study was to determine the role of AhR in a CKD mouse model based on an adenine diet. Wild-type (WT) and AhR−/− mice were fed by alternating an adenine-enriched diet and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The conversion of administered adenine into 2,8-DHA by XDH is the key step in the induction of kidney injury by adenine feeding, which was demonstrated by the amelioration of kidney injury upon treatment with XDH inhibitors [ 31 , 32 ] and by the less severe kidney damage in mice with low expression level of XDH [ 33 ]. Thus, the differences in XDH expression levels observed in our study could modulate the severity of adenine-induced kidney damage and an increased XDH expression level could plausibly be the cause of exacerbated adenine-induced kidney damage in GF mice.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of administered adenine into 2,8-DHA by XDH is the key step in the induction of kidney injury by adenine feeding, which was demonstrated by the amelioration of kidney injury upon treatment with XDH inhibitors [ 31 , 32 ] and by the less severe kidney damage in mice with low expression level of XDH [ 33 ]. Thus, the differences in XDH expression levels observed in our study could modulate the severity of adenine-induced kidney damage and an increased XDH expression level could plausibly be the cause of exacerbated adenine-induced kidney damage in GF mice.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed with knockout mice demonstrated that the animals AhR −/− had moderate renal insufficiency compared to the wild type genes in males, while the difference was even lower in females. This could be explained by the lower level of basal expression of the hepatic enzymes such as p450 cytochrome CYP2E1 and the sulfotransferase SULT1A1 involved in IS production, suggesting that AhR −/− mice have a weak capacity to metabolize indole into IS (Makhloufi et al, 2020).…”
Section: Clinical Approaches For Uremic Toxin Treatmentmentioning
confidence: 99%
“…25,27 In our pilot experiment, we observed significant renal dysfunction among CKD mice as measured by BUN at 4 weeks; however, we also observed a median body weight loss of 31.6% among CKD mice (Figure S1A). Although weight loss is a known limitation of the dietary adenine mouse model of CKD, 11,15,25 we sought to identify a treatment regimen that would result in significant renal dysfunction while minimizing weight loss given its potential as a confounder. We therefore developed a new regimen of intermittent 0.25% dietary adenine exposure by trending BUN and body weight measurements to achieve significant renal dysfunction while limiting weight loss (Figure 1A; Figure S1B and S1C).…”
Section: Dietary Adenine Induces Ckd In C57bl/6 Micementioning
confidence: 77%